2016
DOI: 10.1111/jam.13332
|View full text |Cite
|
Sign up to set email alerts
|

DNA extraction from benthic Cyanobacteria: comparative assessment and optimization

Abstract: These commercial kits allow greater recovery and the elimination of dangerous chemicals for DNA extraction, making them the method of choice for the isolation of DNA from benthic mats. They also facilitate the extraction of DNA from benthic Cyanobacteria, which can help to improve the characterization of Cyanobacteria in environmental studies using qPCRs or population composition analysis using next-generation sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
(45 reference statements)
3
18
1
Order By: Relevance
“…Therefore, ne needs to be careful when using buffers that contain ETDA since this can be found commonly in some elution buffers of commercial kits and in some certain concentrations it may deplete magnesium ions and thus inhibit DNA polymerase activity (Schrader et al 2012). Also, commercial kits are expensive when a large number of samples need to be processed, while the lab made buffer for DNA extraction represent a more economic extraction method if the efficiency criteria is required.Within this study we tested both several commercial kits and a lab made buffer for the cyanobacteria extraction since it was proven that the extracted DNA concentration varied significantly between the commercial kits (Gaget et al 2017), which is also in line with our findings (Table 3, test ).…”
Section: Different Matrix and Dna Extraction Kitssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, ne needs to be careful when using buffers that contain ETDA since this can be found commonly in some elution buffers of commercial kits and in some certain concentrations it may deplete magnesium ions and thus inhibit DNA polymerase activity (Schrader et al 2012). Also, commercial kits are expensive when a large number of samples need to be processed, while the lab made buffer for DNA extraction represent a more economic extraction method if the efficiency criteria is required.Within this study we tested both several commercial kits and a lab made buffer for the cyanobacteria extraction since it was proven that the extracted DNA concentration varied significantly between the commercial kits (Gaget et al 2017), which is also in line with our findings (Table 3, test ).…”
Section: Different Matrix and Dna Extraction Kitssupporting
confidence: 86%
“…Testing the DNA extraction methods is an important and mandatory step no matter what the matrix is, as previous studies showed (Jiang et al, 2005;Gaget et al, 2017), since this represent a critical step in culture-independent bacterial profiling (Hallmaier-Wacker et al 2018). Even if many different protocols and commercially kits have been developed for DNA extractions from environmental samples (Chandraa et al 2010) there is still a lack of reliable techniques for DNA extraction as well for RNA isolation for several types of cyanobacteria (Tiam et al 2019).…”
Section: Different Matrix and Dna Extraction Kitsmentioning
confidence: 99%
“…While DNA extraction method and primer choice can be sources of bias in 16S rRNA gene‐based analyses (Feinstein, Sul, & Blackwood, ; Tremblay et al., ), we believe these are unlikely to be the cause of the relatively low abundance of cyanobacteria in our samples. While calcified cyanobacterial sheaths were abundant in LB microbialites, previous studies of similar systems (e.g., stromatolites, hot springs) found DNA extraction kits that include a physical disruption step (such as the MoBio PowerSoil kit used here) were quite effective at lysing cyanobacterial cell walls (Balskus, Case, & Walsh, ; Gaget, Keulen, Lau, Monis, & Brookes, ; Pepe‐Ranney et al., ). Primer bias against cyanobacteria or specific cyanobacterial classes is also unlikely, as a systematic evaluation of the 515F‐806R primer pair (Bates et al., ) using SILVA's TestPrime tool (Klindworth et al., ) found that these primers matched >87% of existing 16S rRNA gene sequences classified as part of the phylum cyanobacteria in the SILVA SSU Ref NR database (Version 128; Quast et al., ).…”
Section: Discussionmentioning
confidence: 75%
“…While calcified cyanobacterial sheaths were abundant in LB microbialites, previous studies of similar systems (e.g., stromatolites, hot springs) found DNA extraction kits that include a physical disruption step (such as the MoBio PowerSoil kit used here) were quite effective at lysing cyanobacterial cell walls (Balskus, Case, & Walsh, 2011;Gaget, Keulen, Lau, Monis, & Brookes, 2017;Pepe-Ranney et al, 2012). Primer bias against cyanobacteria or specific cyanobacterial classes is also unlikely, as a systematic evaluation of the 515F-806R primer pair (Bates et al, 2011) using SILVA's TestPrime tool (Klindworth et al, 2013) found that these primers matched ites in other locations (Allen et al, 2010;Dupraz & Visscher, 2005).…”
Section: Mramentioning
confidence: 99%
“…Molecular methods also have weaknesses of their own. For instance, the DNA extraction step is an important source of bias in molecular investigations of cyanobacterial assemblages, as high amounts of EPS in the biofilm matrix interfere considerably with cell lysis procedures [54]. Moreover, using data from artificial communities, Pessi et al [26] showed that PCR and sequencing biases shift considerably the observed relative abundances of individual cyanobacterial taxa.…”
Section: Discussionmentioning
confidence: 99%